2010
DOI: 10.1037/a0020896
|View full text |Cite
|
Sign up to set email alerts
|

The functions of nonsuicidal self-injury: Support for cognitive–affective regulation and opponent processes from a novel psychophysiological paradigm.

Abstract: Although research on the reasons for engaging in nonsuicidal self-injury (NSSI) has increased dramatically in the last few years, there are still many aspects of this pernicious behavior that are not well understood. The purpose of this study was to address these gaps in the literature, with a particular focus on investigating whether NSSI (a) regulates affective valence in addition to affective arousal and (b) serves a cognitive regulation function in addition to an affect regulation function. To elucidate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
153
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(173 citation statements)
references
References 57 publications
15
153
3
Order By: Relevance
“…The majority of participants within the community sample studies endorsed cutting and self-hitting as the most common types of NSSI (Franklin et al, 2010;Glenn et al, 2014;Hamza et al, 2014) and within the latter two studies, self-pinching, severe scratching as well as self-hitting were also reported. Little information was given by Bohus et al…”
Section: Type Of Nssimentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of participants within the community sample studies endorsed cutting and self-hitting as the most common types of NSSI (Franklin et al, 2010;Glenn et al, 2014;Hamza et al, 2014) and within the latter two studies, self-pinching, severe scratching as well as self-hitting were also reported. Little information was given by Bohus et al…”
Section: Type Of Nssimentioning
confidence: 99%
“…Only two of the case control studies (Franklin et al, 2010;Glenn et al, 2014) reported any information regarding participants' ethnicity, with their sample being predominantly European American.…”
Section: Sample Characteristics: Ethnicity Age and Gendermentioning
confidence: 99%
See 3 more Smart Citations